Re-description and biology of Parastethynium maxwelli (Hymenoptera: Mymaridae), an egg parasitoid of Zophiuma lobulata (Hemiptera: Lophopidae), and description of a new species of Parastethynium from Indonesia - Huber, John T.; Gitau, Catherine W.; Gurr, Geoff M.; Dewhurst, Charles F.; Fletcher, Murray J. (Zootaxa, 2011)
Both sexes of Parastethynium maxwelli (Girault), a parasitoid of Zophiuma lobulata Ghauri eggs on coconut and oil palm in Papua New Guinea, are described and illustrated. The second known species in the genus Parastethynium, P. hirsutum Huber sp. n., from Indonesia (Sulawesi) is also described. The latter represents the first record from the Oriental region. The basic biology of P. maxwelli is presented. Mean progeny produced per female was 57 with a female proportion of 0.59. Mean egg to adult development time was 11 days, at 24.5 o C−29.7 o C and 72−93% relative humidity. Survival time of females and males fed on honey and water was longer compared to males and differed significantly with those provided with water only or nothing at all.